Idiopathic Spinal Subarachnoid Hemorrhage: A Case Report and Review of the Literature. (October 2015) - Moore, Justin M.; Jithoo, Rondhir; Hwang, Peter
Study Design: Case report. Objective: Spinal subarachnoid hemorrhage (SSAH) makes up less than 1.5% of all the cases of subarachnoid hemorrhage. Most cases of spontaneous SSAH occur in association with coagulopathy, lumbar punctures, or minor trauma. Idiopathic SSAH is extremely rare with only 17 cases published. Idiopathic SSAH presents a diagnostic dilemma, and the appropriate investigations and treatment remain a matter of controversy. We report a case of idiopathic SSAH and a review of the literature regarding its clinical presentation, diagnosis, and treatment. Methods: A 73-year-old woman presented to the emergency department after spontaneously developing severe right leg and lower back pain while bending over to vomit. After a review of the patient's history and examination, the magnetic resonance imaging (MRI) of the thoracolumbar spine revealed T1 hyperintensity and T2 hypointensity, a diffusion-restricted collection at the T11–T12 level, and a posterior collection from L3 to S1 producing a mild displacement of the thecal sac. Results: The patient was taken for an L5 laminectomy. Intraoperatively, rust-colored, xanthochromic fluid was drained from the subarachnoid space, confirming SSAH. The thecal sac was decompressed. The cultures and Gram stains were negative. Computer tomography (CT) and CT angiography of the brain were normal. She recovered postoperatively with resolution of the pain and no further episodes of hemorrhage after 2 years of follow-up. Repeat thoracolumbar MRI, selective spinal angiogram, and six-vessel cerebral angiogram did not reveal pathology. Conclusion: We suggest a clinical algorithm to aid in the diagnosis and management of such patients.